Raising the stakes : Russian military support for Syria - Dorsey, James M. (2012)
Russia is stepping up military support for Syria; reinforcing its opposition to international efforts to force President Bashar al-Assad to halt his eight-month-old crackdown on anti-government protesters. In so doing, Russia is turning the Syrian crisis into an international test of wills.